THE EFFECTIVENESS OF PICTURE CROSSWORD PUZZLE GAME IN TEACHING VOCABULARY - Nugroho, Wahyu; ., Suprapto (ELT Forum: Journal of English Language Teaching, 2017)
This article is based on a study which attempted to examine the effectiveness of the Picture Crossword Puzzle Game in teaching vocabulary. The purposes of this study are to describe the difference in studentsâ vocabulary mastery between those by using Picture Crossword Puzzle Game and conventional method (translation) and to describe the effectiveness of Picture Crossword Puzzle Game in teaching vocabulary. The research design used in this study was a Quasi-Experimental Research. The population of this research was the seventh grade students of SMPN 2 Patebon in the academic year of 2016/2017. The control group was the class of VII-G and the experimental group was the class of VII-H. The results show that from the pre-test, both control and experimental groups have the same mean scores, which is 68.44. After the treatment, there was an increase of mean score of both groups in post-test, which is 81.25 for the control group and 90.94 for the experimental group.The quantitative result shows that the t value is 4.182 and the t table is 1.999. Based on the statistic, it is concluded that there is a sifnificant difference in achievement between both groups. However, this statistic result is not that significant regarding the condition of both control and experimental groups. In other words, the Picture Crossword Puzzle Game has no significant effect on studentsâ vocabulary mastery. Yet, the result of the questionnaire shows that teaching vocabulary using Picture Crossword Puzzle game is interesting for the students. There are 91.8% students who give positive response to Picture Crossword Puzzle Game. In conclusion, the Picture Crossword Puzzle Game can be used to teach vocabulary because this game is interesting.